Understanding Consumer Behavioral Dynamics in Green Marketing Contexts: Evidence from Emerging Markets - Rijal, Trishna; D.C., Samikshya (DAV Research Journal, 2026)
This paper seeks to examine the effect of environmental awareness, green perception, brand loyalty, and economic consequences on the purchasing intentions of consumers. A structured questionnaire was used to do descriptive and causal research. We got primary data from 256 Nepali consumers. We used SPSS to do correlation and regression analyses to see how the variables were related based on the Theory of Planned Behavior. The results show that green perception and economic consequences are the dominant indicators of whether or not someone would consume green products. Although environmental awareness contributes positively, brand loyalty does not significantly affect consumers' decisions to buy green products. The research validates that economic and perceptual factors exert greater influence than emotional brand attachment on green consumer behavior in developing markets such as Nepal. To get more people to use green products, marketers and policymakers could focus on making credible green claims and showing how they can save money. Interventions that increase awareness and lower skepticism can speed up patterns of sustainable consumption. This research adds value to the green consumption in developing economies.